Effect of welding parameters on mechanical properties of welded carbon steel - Muhammad Qaidir, Abdillah (2012)
The main purpose of this project is to study effect of welding parameter on mechanical properties of welded carbon steel. Current problem is cracking happen on the bridge frame after a long time period being used and welding process need to be used to joint back the cracking. The objective of this study is to study the effect of welding parameter such as speed, current and voltage to the mechanical properties of carbon steel. Tensile test, microstructure view, hardness test and optical measurement view is used to define the mechanical properties for welded specimens and as received specimen. The welded specimen being compared with unwelded to study the change of metal before and after welded process. Metal Inert Gas (MIG) welding is used and the liner type was mild steel liner. The hardness study was conducted using a Vickers Hardness Tester MMT-X7 to analyze the conditions change at each region which are weldment zone, heat affected zone and base metal zone area. Low carbon steel show increased in hardness test especially on fusion zone following by heat affected zone due to heating process by the welding. There is a change on microstructure view where the base metal changing and create dendrite shape at weldment area and columnar at heat affected zone area. Optical measurement view test shown the depth of penetration affect the tensile test result. This project is significantly to show that different parameter setup will give different strength and must be the important considered by the welder.